Guaranteed Employment in Rural India: Intra-Household Labor and Resource Allocation Consequences - Jorge Luis García (Institute of Labor Economics (IZA), 2025)
I investigate the intra-household labor and resource allocation consequences of an employment guarantee targeting rural households in India. The guarantee insures household earnings, replacing women as added workers and shutting down a motive for saving. Despite sizable program-job take-up, the guarantee decreases participation in other working activities, and, thus, the labor force participation of married women and total time worked by their husbands. The guarantee accounts for up to 30% of a recent countrywide decrease in rural female labor force participation. Though it increases household consumption, the guarantee reduces the command of household earnings by women, and, thereby, their wellbeing.
Keywords: I31; I32; J12; J13; O12; O15; 330; added-worker effect; family insurance; female labor force participation; guaranteed employment; intra-household bargaining power; poverty